Household fuel use and child respiratory ill health in two towns in Mpumalanga, South Africa - Albers, Patricia Nicole; Wright, Caradee Y; Voyi, Kuku V V; Mathee, Angela (South African medical journal, 2015)
This cross-sectional study examined respiratory health outcomes and associated risk factors in children living in a part of South Africa characterised by high levels of air pollution. A questionnaire was used to collect self-reported respiratory health and risk factor data from the parents/guardians of children between the ages of 9 and 11 years attending primary schools in the study area. Six government schools were selected based on their location, class size and willingness to participate. Univariate and bivariate analyses as well as logistic regression analysis were performed on the data, using a p-value of 0.25 and biological plausibility. The overall prevalence of respiratory ill-health symptoms was 34.1%. The prevalence of respiratory ill-health conditions was significantly elevated among children from households using non-electrical fuels v. electricity for cooking (43.9% v. 31.6%; adjusted p-value 0.005). The same was noted among those using non-electrical fuels for heating (37.8% v. 29.0%). The elevated prevalence of some respiratory health outcomes among schoolchildren, especially in conjunction with domestic fossil fuel burning, is of concern. The data collected in this study may be used to complement or form a basis for future policy regarding indoor or ambient air quality in the area.